Petrology of the Eocene alkaline volcanism from the western Rio Grande Rise, South Atlantic Ocean - Taciro Mandacaru Guerra, Julia; de Assis Janasi, Valdecir; Srivastava, Priyeshu; Stipp Basei, Miguel Angelo; Luvizotto, George Luiz; Jovane, Luigi (Frontiers in Earth Science, 2025)
The origin and evolution of the Rio Grande Rise is deeply related to the opening of the South Atlantic Ocean. The geology of the plateau records the transition from divergent plate margins at the Mid-Atlantic Ridge to an intraplate tectonic setting. Despite the potential to bring insights into the complex tectono-magmatic processes involved in the development of the Rio Grande Rise, there is an overall lack of integrated petrological studies regarding its intraplate Eocene alkaline magmatism. We have investigated trachytes, trachyandesites, alkali basalts, a trachybasalt and a basanite dredged from the western Rio Grande Rise to characterize its magmatic system. Integrated petrography, mineral chemistry and whole-rock geochemistry suggests that these rocks have evolved in a complex transcrustal polybaric magmatic system, where crystals were remobilized by host liquids with different composition at distinct depths. Disequilibrium between crystals and host magmas is evidenced by abundant clinopyroxene macrocrysts with resorbed or corroded cores and rims with contrasting composition, as well as by resorbed feldspar macrocrysts. Clinopyroxene crystals also record cyclic compositional variations in magmatic chambers submitted to multiple magma recharge episodes and a strong control by fractional crystallization. U-Pb dating of zircons from a trachyte yielded an age of 46.9 ± 0.3 Ma, which reinforces the importance of the Eocene volcanism from the western Rio Grande Rise. Moreover, results from Pb, Sr and Nd isotope analysis reveal that Eocene alkaline volcanic rocks from the Western Rio Grande Rise have EMI-flavored Tristan-type signatures. This suggests that the mantle sources from the western Rio Grande Rise and from the Walvis Ridge and Guyot Province magmatism still shared common characteristics long after its separation from the Walvis Ridge.